Severe COVID-19 and its cardiopulmonary effects 6 and 18 months after hospital discharge - Niebauer, J. H.; Iscel, A.; Schedl, S.; Capelle, C.; Kahr, M.; Schamilow, S.; Faltas, J.; Srdits, M.; Badr-Eslam, R.; Lichtenauer, M.; Zoufaly, A.; Valenta, R.; et al. (Frontiers in Cardiovascular Medicine, 2024)
Introduction SARS-CoV-2 infection affects the cardiopulmonary system in the acute as well as long-term phase. The aim of the present study was to comprehensively assess symptoms and possible long-term impairments 6 and 18 months after hospitalization for severe COVID-19 infection. Methods This prospective registry included patients with PCR-confirmed COVID-19 infection requiring hospitalization. Follow-up approximately 6 months post discharge comprised a detailed patient history, clinical examination, transthoracic echocardiography, electrocardiogram, cardiac magnetic resonance imaging (cMRI), chest computed tomography (CT) scan, pulmonary function test (PFT), six-minute walk test (6MWT) and a laboratory panel. At the time of the second follow-up visit at 18 months, patients without pathologic findings during the first study visit were contacted by phone to inquire about the course of their symptoms. In all other patients all initial examinations were repeated. Results Two hundred Patients, who were hospitalized for COVID-19, were contacted by phone and were recruited for the study. Due to dropouts the second study visit was performed in 170 patients. A comparison between the two study visits at 6 and 18 months post discharge showed the following results: Six months after discharge, 73% and 18 months after discharge 52% fulfilled the criteria for Long COVID with fatigue being the most common symptom (49%). Echocardiography at 6 months post discharge showed an impaired left ventricular function in 8% of which 80% returned to normal. Six months post discharge, cMRI revealed pericardial effusion in 17% which resolved in 47% of the 15 patients who underwent a control cMRI. Signs of peri- or myocarditis were present in 5% of the patients and were resolved in all 4 patients who attended control studies. At 6 months, chest CT scans identified post-infectious residues in 24%. In the 25 repeated chest CT scans 20% showed full recovery. Length of in-hospital stay was identified as a significant predictor for persisting Long COVID (95% CI: 1.005–1.12, p = 0.03). Conclusion Comparing 6 to 18 months, the prevalence of Long COVID decreased over time, but a high symptom burden remained. Structural and functional abnormalities were less frequent than the portrayed symptoms, and it thus remains a challenge to substantiate the symptoms.